ANALYSIS OF THE PRODUCTION OF INNOVATIVE PRODUCTS FROM THE FIBERS OF BAR CULTURES - Бойко, Г.А.; Євтушенко, А.В.; Максимченко, Ю.О.; Фурса, О.В. (Modern engineering and innovative technologies, 2024)
In this work, an analysis of the creation of innovative products from bast fiber raw materials of oleaginous flax and technical hemp in the post-war years was carried out. The sown areas occupied by these crops from 2020-2023 were analyzed. It was noted t